2014
DOI: 10.1002/adem.201400012
|View full text |Cite
|
Sign up to set email alerts
|

Color Effects of Nanotextured Aluminum Surfaces: Characterization and Modeling of Optical Behavior

Abstract: International audienceSurface finishes based on structural colors raise interest in product design and architecture in that long lasting colored surfaces can be produced with low risks if color fading. In this paper, aluminum surface are patterned through anodization with additional chemical post-treatment. This electrochemical technique is advantageous in that it is already industrially mature and enables the treatment of large surfaces. The resulting surface shows self-organized nanopatterns that lead to spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Moreover, we observed that the serpentine structures deposited with different parameters show different structural colors under irradiation of light. The structural colors may be attributed to the effect of scattered light or thin-film interference [33,34].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observed that the serpentine structures deposited with different parameters show different structural colors under irradiation of light. The structural colors may be attributed to the effect of scattered light or thin-film interference [33,34].…”
Section: Resultsmentioning
confidence: 99%